2000
DOI: 10.1002/1097-4644(20001101)79:2<213::aid-jcb50>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

The multi-PDZ domain protein MUPP1 is a cytoplasmic ligand for the membrane-spanning proteoglycan NG2

Abstract: A yeast two-hybrid screen was employed to identify ligands for the cytoplasmic domain of the NG2 chondroitin sulfate proteoglycan. Two overlapping cDNA clones selected in the screen are identical in sequence to a DNA segment coding for the most amino-terminal of the 13 PDZ domains found in the multi-PDZ-protein MUPP1. Antibodies made against recombinant polypeptides representing these two clones (NIP-2 and NIP-7) are reactive with the same 250-kDa molecule recognized by anti-MUPP1 antibodies, confirming the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 56 publications
2
60
1
Order By: Relevance
“…Furthermore, the ¢rst PDZ of MUPP1 is a member of the most abundant group (G,H); therefore it should bind to class I motifs. In contrast, our computer-aided analysis [1] and two hybrid (in vitro) and co-immunoprecipitation (in vivo) assays [4] indicate a preference of MUPP1-1 PDZ domain for class II ligands, such as NG2 proteoglycan. Another example is CIPP-3 PDZ domain that is classi¢ed as (G,p) and therefore it should prefer peptides related to the consensus (8Dx*); in contrast, it interacts with Kir4.2 channel and NR2 (type A-B-C-D) receptors that have class I extremities [5].…”
contrasting
confidence: 61%
“…Furthermore, the ¢rst PDZ of MUPP1 is a member of the most abundant group (G,H); therefore it should bind to class I motifs. In contrast, our computer-aided analysis [1] and two hybrid (in vitro) and co-immunoprecipitation (in vivo) assays [4] indicate a preference of MUPP1-1 PDZ domain for class II ligands, such as NG2 proteoglycan. Another example is CIPP-3 PDZ domain that is classi¢ed as (G,p) and therefore it should prefer peptides related to the consensus (8Dx*); in contrast, it interacts with Kir4.2 channel and NR2 (type A-B-C-D) receptors that have class I extremities [5].…”
contrasting
confidence: 61%
“…Plasmid Constructions and Cell Culture-The GW1-HA-MUPP1 plasmid containing the coding region of the rat MUPP1 as well as GST fusion constructs expressing PDZ1-3, PDZ4-5, PDZ6, PDZ7, or PDZ8-9 were a gift from Dr. Javier and have been described elsewhere (22,23). GST fusion constructs containing PDZ9, PDZ10, or PDZ11-12 were a gift from Dr. Mancini (24).…”
Section: Methodsmentioning
confidence: 99%
“…Receptor immunoprecipitation was done on supernatant by the anti-FLAG M2 antibody (Sigma) preadsorbed on Protein G. Immunoadsorbed material was pelleted by centrifugation, submitted to SDS-PAGE, and transferred to nitrocellulose. Immunoblot analysis was carried out with the polyclonal anti-MUPP1 antiserum at 1:20,000 dilution (a gift from Dr. Javier) (22,23) or the polyclonal anti-FLAG antibody (Sigma), and immunoreactivity was revealed using a goat anti-rabbit secondary antibody coupled to horseradish peroxidase and the ECL chemiluminescent reagent (Amersham Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…MUPP1 was initially identified as a protein that interacts with the COOH terminus of the serotonin 5-hydroxytryptamine type 2C receptor (44,45,52). This protein was also reported to be associated with c-Kit (50), the membrane-spanning proteoglycan NG2 (53), and adenovirus E4-ORF1 and high-risk papillomavirus type 18 E6 oncoproteins (54) but has not been well characterized, especially in terms of its subcellular localization. In this study, we generated a pAb specific for MUPP1, and by immunofluorescence as well as immunoelectron microscopy we concluded that in simple epithelial cells MUPP1 is concentrated at TJs, favoring the in vivo interaction between MUPP1 and claudins.…”
Section: Generation and Evaluation Of Anti-mupp1 Pab-to Exam-mentioning
confidence: 99%